Genetic diversity analysis of Indian buffalo breeds By microsatellite markers - Rupinder; M. L. Sangwan (Journal of Livestock Biodiversity, 2025)
The present study was conducted on 20 unrelated animals each of Bhadawari and Murrah breeds to estimategenetic diversity parameters by microsatellite markers. Ten microsatellites markers recommended by FAO forbuffalo diversity were used. The number of alleles in both the breeds per locus ranged from 3 to 6. The averagenumbers of alleles were 4.2 ± 0.38 for Bhadawari and 4.2 ± 0.44 for Murrah breed. The mean observedheterozygosity was 0.49 for Bhadawari and 0.53 for Murrah breed. The average expected heterozygosity was 0.57and 0.59 for Bhadawari and Murrah breed, respectively. The observed heterozygosity values in both breeds werelowest for the loci ILSTLS008 and CSSM029. The overall mean heterozygosity in both breeds was 0.51. The averagePIC value for all loci was 0.51 in Bhadawari and 0.52 in Murrah breeds. In the present study, 70 per cent of themicrosatellite markers were found to be highly informative. Seven loci showed deviations from the HWE for the lociILSTLS008, BRN, CSSM029, CSSM019, CSSM036, CSSM047 and CSSM038. The mean FIS, FIT and FST for all loci was– 0.12, 0.16 and 0.04, respectively. The standard genetic distance (Ds) between Bhadawari and Murrah breeds was0.13 and the genetic identify was 0.88.